The handbook of experiential learning (Pfeiffer, 2007)
The Handbook of Experiential Learning is a comprehensive resource that draws together contemporary thought and practice on a wide range of experiential learning applications from the best-known authorities on the topic. In this book, volume editor and leading experiential learning expert, Mel Silberman presents a contemporary review of experiential learning in the workplace complete with models, applications, and innovative uses.